Ang maglandi ay 'di biro the kalandian chronicles : manual para sa mga one-sided lovers - Hernandez, Dani (Mandaluyong City Anvil Publishing, Incorporated, 2015)
"Aminin mo na. Anong klaseng nilalang ka man, paniguradong minsan (o madalas) sa buhay mo eh naging one-sided lover ka! Kung ikaw ay nasaktan, umasa, pinaasa, umiyak, na-depress, na-brokenhearted, nagpakamartir, naging forever alone, NBSB, binigay ang lahat, niloko, winasak at umibig mag-isa? Para 'to sa'yo. Hindi madali... Hindi nakakatawa... Dahil pag ganito ang setup... Ang paglalandi ay mahirap... Dahil ang maglandi ay 'di biro. Promise."
PROLOGUE -- PART I: The Prelude. -- Chapter one: Show me the true meaning of love. -- Chapter two: One way or another. -- PART II: The unrequited. -- Chapter three: Just a little bit of your heart is all I want. -- Chapter four: Am I crazy or falling in love? Is it real or just another crush? -- Chapter five: An now I'm fallin', fallin', catch me if you can. -- Chapter six: Bahay kubo, kahit munti, ang malalandi doon ay sari-sari. -- PART III: The downside. -- Chapter seven: Me and my broken heart. -- Chapter eight: Don't give me this feeling, I'll only believe it, make it real, or take it all away. -- Chapter nine: You're insecure, Don't know what for. -- Chapter ten: Tell me where it hurts. -- Chapter eleven: It's okay not to be okay. -- Chapter twelve: Got a long list of ex-lovers. -- PART IV: The hugot. -- Chapter thirteen: underneath your clothes, there's an endless story. -- Chapter fourteen: I want to see you be brave. -- PART V: FAQs. -- Chapter fifteen: For these are the questions we've got to face. -- PART VI: The end. -- Epilogue: Love comes to those who believe it and that's the way it is.
Keywords: Unrequited love -- Juvenile literature. -- Handbooks, manuals, etc; Flirting in literature